Development and experimental study of a self-centering variable damping energy dissipation brace. (1st April 2018) - Xu, Long-He; Xie, Xing-Si; Li, Zhong-Xian
Highlights: A self-centering variable damping energy dissipation (SC-VDED) brace is proposed. A series of cyclic tests of a large-scale SC-VDED brace specimen were carried out. Brace exhibits quasi-flag-shaped hysteretic responses with large energy dissipation. Fatigue and destructive tests demonstrate that brace has stable seismic behaviors. Abstract: A new self-centering variable damping energy dissipation (SC–VDED) brace is proposed to reduce the activation force and sudden change in stiffness after activation of self-centering energy dissipation braces. The brace uses the combination disc springs to provide self-centering capability and the structural design of a magnetorheological (MR) fluid device to realize variable damping energy dissipation. The mechanics of the SC–VDED brace and the equations governing its design and hysteretic responses are presented. A brace specimen with a total length of 1.365 m was designed and fabricated, and a series of cyclic tests were carried out under the sinusoidal excitation with different frequencies and amplitudes. Results demonstrate that the brace exhibits full quasi-flag-shaped hysteretic responses, a small activation force, few sudden change in stiffness, and large energy dissipation. The pre-pressed force of the combination disc springs should be larger than the initial damping force, and their stiffness should be increased to give full play to the self-centering and energy dissipation capabilities of the brace. Fatigue and destructive test results indicate that the behaviors of the brace are stable enough to provide self-centering and energy dissipation capabilities, and the loose and severe stress concentration of the outer tube clamps cause the brace to fail.